COVID‑19 and the financial resilience of Finland’s seaports - Leviäkangas Pekka; Ojala Lauri; Paik Seong Mok; Pekkala Veikko (Springer, 2025)
This research quantifies the impacts that COVID-19 had on the financial performance of Finnish seaports. The data comprises annual financial statement information from 18 seaports. The ports are different in terms of ownership, size, and main lines of business. Most ports’ turnover dropped because of COVID-19, and their profitability declined. However, the ports were able to maintain their financial position quite well despite their declining turnovers. Statistically significant impacts of COVID-19 were observable regarding turnover growth, profitability, labor intensity and capital intensity. Surprisingly, ports with mainly import traffic had the least negative impacts on turnover growth.
Keywords: Port performance, Financial analysis, COVID-19, Finland